Extraction and modification of gum from cashew tree exudates using wheat starch and glycerine - Andri Cahyo Kumoro; Diah Susetyo Retnowati; Catarina Sri Budiyati (Jurnal Rekayasa Proses, 2010)
The objectives of this research were to extract cashew tree gum (CTG) from cashew tree exudates and to modify it into a new drying aid, which can act as a substitute for Arabic gum. The cost problem faced in the spray drying of fruit juices is expected to be solved with the use of modified CTG as a replacement of Arabic gum. The CTG was extracted and precipitated from its raw cashew exudates solution with the help of ethanol as antisolvent. Glycerine and wheat starch were the additives used in the modification of the gum. The good quality of modified CTG was obtained based on their close similarity to Arabic gum properties.